Fuzzy Linear Programming Problem ( Discussion and Application) (Al-Mansour Journal, 2022)
We know that the linear programming model (LPM) is one of the most approach used in operation research and decision making, it represent a mathematical model for finding optimum allocation of resources, to satisfy certain objective, like maximize profit or minimize cost. In (LPM), we consider all coefficients of operation function and constraints are real but in real life problem, the wright hand side of (LP), and coefficients of variables of operation function may be a fuzzy number, so this research deals with explaining fuzzy linear programming model with definitions of required and with operation on fuzzy number, then how to solve fuzzy linear programming.
Keywords: Fuzzy linear programming; triangular and trapezoidal fuzzy numbers; Ranking Function